Seasonal Evaluation of Trace Metals in Irrigated Soils at Various Sites in Phuleli Command Area (Sindh), Pakistan - Ashifa Soomro; Altaf Ali Siyal; Muhammad Saffar Mirjat; Allah Wadhayo Gandahi; Rabail Gandahi (Journal of Basic & Applied Sciences, 2015)
Phuleli Canal (Sindh) Pakistan is the main source of irrigation water for lower Sindh. However, its quality has been deteriorated by the addition of industrial effluents and city wastes discharged directly or indirectly into canal when it passes through Hyderabad city. For monitoring the effect of this canal water on soil quality of the command area, the present study was designed to evaluate the seasonal variability of trace metals including Cu, Fe, Zn and Mn in the cultivated soil area. The soil samples were collected from different seven sites (reduced distance, RD = 304.8 m) RD-0, RD-30, RD-50, RD-70, RD-90, RD-110 and RD-130) in four seasons (summer, autumn, winter, and spring) and analysed for Cu, Fe, Zn and Mn contents. Then, the obtained results were compared with the maximum permissible values of FAO for agriculture/crop production. Results showed that the Zn contents in soil samples was relatively higher than FAO permissible limits during winter in all soil layers and all sites mostly at upper reach sites of Phuleli Command area. While, the Fe content in soil at all depths was found higher during winter, autumn and spring. Whereas, in summer season it was relatively more in upper soil layers near mid to down reach sites and were not within the permissible limits of FAO. Same was true with Cu and Mn which were also not within the permissible limits of FAO for crop production. So, it was inferred that almost of the locations trace elements in soils found higher under Phuleli Canal Command area were mainly produced from various pollution sources viz, industrial and municipal liquid effluents.